Evaluation of the efficacy and safety of cryopreserved deglycerolized red blood cells infusion based on propensity score matching method - YANG Wei; FU Fanfan; NIU Lei; XU Tingchen; ZHANG Xin; SHI Hongmei; FU lihui; MA Chunya; YU Yang (Zhongguo shuxue zazhi)
[Objective] To compare the efficacy and safety of deglycerolized red blood cells (DRBC) and suspended red blood cells (SRBC) based on the propensity score matching (PSM) method, so as to provide evidence for the rational use of DRBC resources in clinical practice. [Methods] A total of 89 patients who received DRBC transfusion and 2 916 patients who received SRBC transfusion in our hospital from January 2023 to September 2024 were included. A 1∶1 nearest neighbor PSM was used to balance covariates such as gender, age, and body mass index (BMI). The changes of hemoglobin (Hb), red blood cell (RBC) count, hematocrit (HCT), and inflammatory markers such as white blood cell (WBC) count, neutrophil (NE) count, C-reactive protein (CRP), and Interleukin-6(IL-6) in the last 72 hours after transfusion were analyzed by SPSS 26.0 and R software to evaluate clinical efficacy and transfusion safety. [Results] The baseline of the two groups was balanced after PSM (P>0.05). There was no significant difference in the total effective rate between the DRBC group (80.9%) and the SRBC group (86.5%) (P>0.05). In the SRBC group, WBC (×109/L) increased from 9.634±6.742 to 10.147±6.835, CRP (mg/dL) increased from 5.468±4.647 to 6.174±6.114, and IL-6(pg/mL) decreased from 213.733±587.191 to 157.255±552.626. In the DRBC group, WBC (×109/L) decreased from 11.123±7.880 to 11.011±8.549, CRP (mg/dL) decreased from 5.729±4.761 to 5.326±4.466, and IL-6(pg/mL) decreased from 238.806±639.060 to 152.255±266.558. Compared with the before treatment, the differences between the SRBC group and DRBC group were not statistically significant (P>0.05). Among all patients included in the statistics, the overall incidence of transfusion adverse reactions was 0.205% (6/2 916) in the SRBC group, and no adverse reactions occurred in the DRBC group. The incidence in the SRBC group was higher than that in the DRBC group. [Conclusion] Based on PSM analysis, there was no significant difference in the efficacy and safety of DRBC transfusion compared with SRBC transfusion, which can provide evidence-based support for routine application.